Exploring the Link between Trust and Perceived Benefits in Online Purchasing during COVID-19 - Tegowati, Tegowati (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the impact of perceived benefits on online consumer purchasing decisions during the COVID-19 pandemic in Surabaya, Indonesia. The study examines the role of social media as a tool for marketers to support product sales during the pandemic, which aligns with government regulations to limit community activities that cause crowds. The study uses trust as an intervention variable to analyze the direct and indirect impacts of perceived benefits on purchasing decisions. The research is conducted using a purposive sampling method, and data from 100 online consumers in Surabaya is analyzed using Structural Equation Modeling (SEM). The findings indicate that perceived benefits have a direct and significant impact on trust, perceived benefits have a direct and significant impact on purchasing decisions, trust directly influences purchasing decisions, and perceived benefits have a significant direct impact on consumer online purchasing decisions with trust acting as an intervening variable. The study provides valuable insights for marketers in utilizing social media to support product sales during a pandemic and highlights the importance of trust in online purchasing decisions.